Iron ore slime as an alternate coolant in steelmaking: Performance evaluation at commercial scale. (15th December 2016) - Rajshekar, Y.; Alex, T.C.; Sahoo, D.P.; Babu, G. Anand; Balakrishnan, V.; Venugopalan, T.; Kumar, Sanjay
Abstract: This paper describes an attempt to utilize iron ore slime in basic oxygen steelmaking as a coolant (instead of lump iron ore). Prior to its use, it is briquetted for ease of charging. The tests are carried out in a regular, commercial basic oxygen steelmaking furnace (160 ton/batch, and duration about 45 min). Substitution of lump ore (with slime briquette) in various tests has been in the range of 30–100%. Results – turn down temperature is well maintained, phosphorous is below the target limit, lime consumption is similar to that with lump ore-indicate that slime briquette is a good coolant and can substitute the scarcely available lump ore in steelmaking. Thus, 10–15% of the slime generated can be gainfully utilized in the steelmaking process. This will make the lump ore (used in steelmaking) available for blast furnace iron making. This approach, an eco-innovation (involving an innovative practice combining economic and ecological-resource benefits) is a sustainable solution to the burgeoning slime accumulation, and makes iron and steel sector industries less vulnerable to environmental regulations. Highlights: Discarded iron ore slime is useful as an efficient coolant in steel making. An innovative practice combining economic and ecological-resource benefits. Cost effectiveness and adequate availability shows its commercial potential. Resource conservation and reduced environmental burden lead towards sustainability.